Memorandum of understanding between Universiti Teknologi MARA and Universitas Gadjah Mada / Fakulti Kejuruteraan Awam - Universiti Teknologi MARA, Fakulti Kejuruteraan Awam (Universiti Teknologi MARA (UiTM), 2019)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.